A previously undescribed organic residue sheds light on heat treatment in the Middle Stone Age. Issue 85 (August 2015) - Schmidt, Patrick; Porraz, Guillaume; Bellot-Gurlet, Ludovic; February, Edmund; Ligouis, Bertrand; Paris, Céline; Texier, Pierre-Jean; Parkington, John E.; Miller, Christopher E.; Nickel, Klaus G.; Conard, Nicholas J.
Abstract: South Africa has in recent years gained increasing importance for our understanding of the evolution of 'modern human behaviour' during the Middle Stone Age (MSA). A key element in the suite of behaviours linked with modern humans is heat treatment of materials such as ochre for ritual purposes and stone prior to tool production. Until now, there has been no direct archaeological evidence for the exact procedure used in the heat treatment of silcrete. Through the analysis of heat-treated artefacts from the Howiesons Poort of Diepkloof Rock Shelter, we identified a hitherto unknown type of organic residue – a tempering-residue – that sheds light on the processes used for heat treatment in the MSA. This black film on the silcrete surface is an organic tar that contains microscopic fragments of charcoal and formed as a residue during the direct contact of the artefacts with hot embers of green wood. Our results suggest that heat treatment of silcrete was conducted directly using an open fire, similar to those likely used for cooking. These findings add to the discussion about the complexity of MSA behaviour and appear to contradict previous studies that had suggested that heat treatment of silcrete was a complex (i.e., requiring a large number of steps for its realization) and resource-consuming procedure.